Hubungan Kebiasaan Sarapan, Kualitas Tidur, dan Body Image dengan IMT/U Remaja di SMAN 32 Jakarta - Cita Zahra Ayu Wikanti; Said, Irfan; Khairunnisa, Azkaa (Kabar Gizi Indonesia, 2024)
Nutrition is a health problem that often occurs in adolescence and adulthood. Nutritional problems in adolescents can occur due to several factors, such as breakfast habits, perception of body image, and sleep quality. The purpose of this study was to analyze whether there is a relationship between breakfast habits, sleep quality, and body image with BMI for Age in adolescents at SMA Negeri 32 Jakarta. This study used an analytic correlation research design with a cross sectional approach. The sampling technique used purposive sampling with a total sample of 184 adolescents. The results showed that there was no significant relationship between breakfast habits and adolescent BMI for Age (p-value = 1.000), there was no significant relationship between sleep quality and adolescent BMI for Age (p-value = 0.441), there was no significant relationship between body image and adolescent BMI for Age (p-value = 0.162).